Option A
If f(x) =
and g(x) =
then
![(f - g)(x) = x^2 + 8](https://img.qammunity.org/2020/formulas/mathematics/middle-school/lelqlkbmv8tk6avy9z3rltnow6titvpbql.png)
Solution:
Given that f(x) =
and g(x) =
![x^2 - 7](https://img.qammunity.org/2020/formulas/mathematics/middle-school/h3gdovgsc9x3l055to7zdlecwfswq34nkq.png)
To find: (f - g)(x)
We know that,
(f – g)(x) = f (x) - g(x)
Let us substitute the given values of f(x) and g(x) in above formula,
![(f - g)(x) = 2x^2 + 1 - (x^2 - 7)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/6loi3b4r1bxar7gfs2sg3kfpdfb23rnh6u.png)
For solving the brackets in above expression,
There are two simple rules to remember:
When you multiply a negative number by a positive number then the product is always negative.
When you multiply two negative numbers or two positive numbers then the product is always positive.
So the expression becomes,
![(f - g)(x) = 2x^2 + 1 -x^2 + 7](https://img.qammunity.org/2020/formulas/mathematics/middle-school/dadcbxmb0iuf2m4p7vnj5fag444clb0bap.png)
Combining the like terms,
![(f - g)(x) = 2x^2 - x^2 + 1 + 7\\\\(f - g)(x) = x^2 + 8](https://img.qammunity.org/2020/formulas/mathematics/middle-school/w8ox5qaf7mzy27k6m8xb56oosz66j83mhv.png)
Thus option A is correct